PENGARUH PERSEPSI, MOTIVASI, MINAT, DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPUTUSAN MAHASISWA BERKARIR DIBIDANG PERPAJAKAN PADA MAHASISWA AKUNTANSI UNIVERSITAS WIJAYA KUSUMA SURABAYA - Uzlifa Musarrofi; Iman Karyadi (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the influence of perception, motivation, interest, and tax knowledge on students' decisions to pursue careers in the taxation field among Accounting Study Program students at Wijaya Kusuma University Surabaya. The study employed a quantitative approach using a survey method by distributing questionnaires to students from the 2023 and 2024 cohorts who had completed taxation courses. The sampling technique used was purposive sampling, resulting in a total of 75 respondents. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that motivation and tax knowledge have a positive and significant effect on students' decisions to pursue careers in taxation. Meanwhile, perception and interest have a positive but statistically insignificant effect on career decisions in the taxation field. These findings suggest that students' internal motivation and adequate tax knowledge are the main factors influencing career decisions in the taxation sector. This study provides implications for higher education institutions to improve the quality of taxation learning and to provide programs that can enhance students' motivation to pursue careers in taxation.